Machine learning : proceedings of the seventh international conference (1990), University of Texas, Austin, Texas, June 21-23, 1990 - Porter, Bruce, 1956-; Mooney, Raymond J. (Raymond Joseph) (Morgan Kaufmann Publishers, 1990)
Machine Learning Proceedings 1990.